Effects of quail genotypes on hatchability traits, body weight and egg production (Journal of Bangladesh Academy of Sciences, 2014)
A study was conducted with four genotypes of quail, namely Japanese (J), White (W), Black (Bl) and Brown (Br) quail with the objective to know their hatchability traits, body weight and egg production performances. The parent males and females were maintained in cages for single pair mating through close breeding system for producing each generation. A total of 1866-day-old chicks comprising of 4 types of quail namely J, W, Br, and Bl were hatched in a batch. The egg weight were 10.35 ± 0.3, 11.60 ± 0.42, 10.30 ± 0.42 and 9.78 ± 0.65 for J, W, Br and Bl respectively, which was influenced (p < 0.05) by genotype. White genotype of quail is significantly better for egg weight, chick weight and chick: egg ratio than that of their counterparts. The highest hatchability of incubated eggs was found in Japanese quail genotype (71.01%) and the lowest in Black (31.03%). Significantly higher body weight was found in White and Black followed by Brown and Japanese quail genotype at different period of age. Significantly more number of eggs was obtained in Black (97.31) followed by Japanese, Brown and White respectively DOI: http://dx.doi.org/10.3329/jbas.v38i2.21346 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 219-224, 2014